INFLUENCE OF SILICA BASED WASTE MATERIALS ON THE MECHANICAL AND PHYSICAL PROPERTIES OF MORTAR - S.I., Balang; Norsuzailina, Mohamed Sutan; Ibrahim, Yakub; M.S., Jaafar; K.A., Matori (UNIMAS Publisher, 2022)
This is an investigation on the influence of silica based waste materials namely silica fume (SF) and recycled vase (RV) on the physical and mechanical properties of mortar. Results showed that 15%SF modified mortar achieved the highest strength and lowest water absorption capability compared to Control mortar and other mixtures. The result was confirmed by water absorption capability test for the same mixtures where 15% SF modified mortar was found to absorb the least. Furthermore, combination of 15% SF and 10% RV achieved the lowest water absorption compared to other combinations samples but higher than Control and 15% SF modified mortar. The results of this study indicated that SF is highly pozzolanic material that can be an excellent cement replacement material to produce high- performance concrete. Study on pozzolanc behavior of SF samples subjected to longer hydration time is needed. Further microstructural investigation is needed to confirm the hypothesis on retardation of hydration due to unreactive RV.